Perceptions of prescription warning labels within an underserved population - Shiyanbola OO; Meyer BA; Locke MR; Wettergreen S (Centro de Investigaciones y Publicaciones Farmaceuticas, 2014)
Objective: To understand how underserved populations attend to prescription warning label (PWL) instructions, examine the importance of PWL instructions to participants and describe the challenges associated with interpreting the information on PWLs. Methods: Adults from an underserved population (racial and ethnic minorities, individuals with low income, older adults) who had a history of prescription medication use and were able to understand English took part in semi-structured interviews. Participants were presented with eight different prescription bottles with an attached PWL. Participants were asked, "If this prescription was yours, what information would you need to know about the medicine?" The number of participants who attended to the warning labels was noted. Other questions assessed the importance of PWLs, the challenges with understanding PWLs, and ways a pharmacist could help participant understanding of the PWL. Results: There were 103 participants. The mean age was 50.25 years (SD=18.05). Majority attended to the PWL. Participants not currently taking medications and who had limited health literacy were likely to overlook the warning labels. Majority rated the warning instructions to be extremely important (n=86, 83.5 %), wanted the pharmacist to help them understand PWLs by counseling them on the information on the label (n=63, 61.2%), and thought the graphics made the label information easy to understand. Conclusions: PWLs are an important method of communicating medication information, as long as they are easily comprehensible to patients. In addition to placing PWLs on prescription bottles, health care providers need to counsel underserved populations on medication warnings, especially individuals with limited health literacy who are not currently using a prescription medication.